Pulmonary and Hepatic Gene Expression following Cecal Ligation and Puncture: Monophosphoryl Lipid A Prophylaxis Attenuates Sepsis-Induced Cytokine and Chemokine Expression and Neutrophil Infiltration - Salkowski, Cindy A. (American Society for Microbiology, 1998)
Polymicrobial sepsis induced by cecal ligation and puncture (CLP) reproduces many of the pathophysiologic features of septic shock. In this study, we demonstrate that mRNA for a broad range of pro- and anti-inflammatory cytokine and chemokine genes are temporally regulated after CLP in the lung and liver. We also assessed whether prophylactic administration of monophosphoryl lipid A (MPL), a nontoxic derivative of lipopolysaccharide (LPS) that induces endotoxin tolerance and attenuates the sepsis syndrome in mice after CLP, would alter tissue-specific gene expression post-CLP. Levels of pulmonary interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), granulocyte colony-stimulating factor (G-CSF), IL-1 receptor antagonist (IL-1ra), and IL-10 mRNA, as well as hepatic IL-1β, IL-6, gamma interferon (IFN-γ), G-CSF, inducible nitric oxide synthase, and IL-10 mRNA, were reduced in MPL-pretreated mice after CLP compared to control mice. Chemokine mRNA expression was also profoundly mitigated in MPL-pretreated mice after CLP. Specifically, levels of pulmonary and hepatic macrophage inflammatory protein 1α (MIP-1α), MIP-1β, MIP-2, and monocyte chemoattractant protein-1 (MCP-1) mRNA, as well as hepatic IFN-γ-inducible protein 10 and KC mRNA, were attenuated in MPL-pretreated mice after CLP. Attenuated levels of IL-6, TNF-α, MCP-1, MIP-1α, and MIP-2 in serum also were observed in MPL-pretreated mice after CLP. Diminished pulmonary chemokine mRNA production was associated with reduced neutrophil margination and pulmonary myeloperoxidase activity. These data suggest that prophylactic administration of MPL mitigates the sepsis syndrome by reducing chemokine production and the recruitment of inflammatory cells into tissues, thereby attenuating the production of proinflammatory cytokines.